Controlled Carbonization Heating Rate for Enhancing CO2 Separation Based on Single Gas Studies - Wan Nurul Huda, Wan Zainal; Tan, Soon Huat; Mohd Azmier, Ahmad (Budapest University of Technology and Economics, 2019)
Concerns about the impact of greenhouse gas have driven the development of new separation technology to meet CO2 emission reduction targets. Membrane-based technologies using carbon membranes that are able to separate CO2 efficiently appears to be a competitive method. This research was focused on the development of carbon membranes derived from polymer blend of polyetherimide and polyethylene glycol to separate CO2 rendering it suitable to be used in many applications such as landfill gas purification, CO2 removal from natural gas or flue gas streams. Carbonization process was conducted at temperature of 923 K and 2 h of soaking time. To enhance membrane separation properties, pore structure was tailored by varying the carbonization heating rates to 1, 3, 5, and 7 K / min. The effect of carbonization heating rate on the separation performance was investigated by single gas permeabilities using CO2 , N2 , and CH4 at room temperature. Carbonization heating rate of 1 K / min produced carbon membrane with the most CO2 / N2 and CO2 / CH4 selectivity of 38 and 64, respectively, with the CO2 permeability of 211 barrer. Therefore, carbonization needs to be carried out at sufficiently slow heating rates to avoid significant loss of selectivity of the derived carbon membranes.